BS6 Coherent vortex flow in the adult right atrium. (4th June 2021) - Gan, Lian; Dewhurst, Peter; Coats, Louise; Parikh, Jehill; Hollingsworth, Kieren
Abstract : Brief introduction: In healthy adults, the right atrium (RA) serves as a reservoir for the systemic flow return from the superior vena cava (SVC) and inferior vena cava (IVC), preparing the two flows to be transferred to the right ventricle (RV) and pulmonary circulation. This study aims to quantify the haemodynamics of the RA and the associated SVC and IVC inflows, which have not been fully understood to date. Basic Methods: Eighteen adults with structurally normal hearts underwent 4D flow magnetic resonance imaging. The cardiac cycle was resolved to 20 temporal phases with a spatial resolution of 3×3×3 mm cube. Analysis included objective visualisation of the flow structures in the RA identified by three different vortex identification criteria, kinetic energy (KE), enstrophy and dissipation. KE and helicity flux were also assessed in both caval veins. Main Results: Vortex identification methods confirmed that in the majority of participants the blood flow from the caval veins filling the RA during ventricular systole is not chaotic, but rather forms an organised pattern of a single coherent forward turning vortex structure. Thirteen participants displayed a single vortex flow structure, four showed multiple vortices and one had a helical flow pattern without a clear vortex structure. A strong positive correlation exists between the flow KE and enstrophy density. Conclusions and Implications: This study suggests that flow energy in the RA is mainly rotational, part of which is convected by the highly helical SVC and IVC inflows. Multiple vortices tend to be associated with higher dissipation rates in the central RA region due to turbulence. The rotational nature of the flow in the RA maintains KE better than non-rotational flow. RA flow characteristics are highly related to the helicity content in the caval veins, as well as the KE flux intensity. Lower caval helicity or IVC KE flux dominance tends to favour single vortex formation while the opposite tends to lead to multiple vortices or the rare helical flow patterns. Atria lacking single vortex flow are inclined to have a larger energy input from atrial contraction. Conflict of Interest: n/a